2019
DOI: 10.1186/s42269-019-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the changes in potential environmental risk of some heavy metals in water and sediments of Burullus Lake, Egypt

Abstract: Background: Burullus Lake has received a great attention because of its environmental and economic importance for connecting with the Mediterranean Sea through El Boughaz opening. Some of the chemical analyses were performed to study the potential environmental risk of Burullus Lake. The present study explores the potentiality of environmental risk of Fe, Mn, Co, Ni, Cr, Cd, Pb, Zn, and Cu for detecting most vulnerable areas to water and sediment pollution at Burullus Lake during different three periods: 2010,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Heavy metals estimated levels (Fe, Zn, Pb, Cu, and As) in the water of Burullus Lake and fish farm were within the standard allowed values except for Pb, which exceeded the maximum permitted levels (WHO, 2011), as a result of contamination by industrial effluents and municipal sewage concentrations that might be blamed (Chen et al, 2010;Nafea and Zyada, 2015). Moreover, HM levels in the current study's findings (Burullus Lake and Farmed fish waters) are still within the range of prior examinations, except for Zn, Cu, and Pb, which were greater in both analyzed locations than in past studies (Younes and Nafea, 2012;Ghabour et al, 2013;El-Batrawy et al, 2018;Melegy et al, 2019). The following is the order of the metals: Fe < Zn < Pb < Cu < As < Cd as reported in other studies (Darwish, 2016;El Morshedy, 2017;El-Batrawy et al, 2018).…”
Section: Assay Of Heavy Meals In Water and Fish Tissuessupporting
confidence: 71%
“…Heavy metals estimated levels (Fe, Zn, Pb, Cu, and As) in the water of Burullus Lake and fish farm were within the standard allowed values except for Pb, which exceeded the maximum permitted levels (WHO, 2011), as a result of contamination by industrial effluents and municipal sewage concentrations that might be blamed (Chen et al, 2010;Nafea and Zyada, 2015). Moreover, HM levels in the current study's findings (Burullus Lake and Farmed fish waters) are still within the range of prior examinations, except for Zn, Cu, and Pb, which were greater in both analyzed locations than in past studies (Younes and Nafea, 2012;Ghabour et al, 2013;El-Batrawy et al, 2018;Melegy et al, 2019). The following is the order of the metals: Fe < Zn < Pb < Cu < As < Cd as reported in other studies (Darwish, 2016;El Morshedy, 2017;El-Batrawy et al, 2018).…”
Section: Assay Of Heavy Meals In Water and Fish Tissuessupporting
confidence: 71%
“…Consistent with previous findings (Melegy et al, 2019), our results showed that pH was alkaline (8.6-9 and 7.8-8.8 during winter and summer, respectively) probably because of the increased photosynthetic activity of phytoplankton in the lake or the chemical nature of water (Al-Sheikh & Fathi, 2010;Nassar & Gharib, 2014). The water of Burullus Lagoon was considered a well-oxygenated ecosystem in both seasons in this study 1mg/L in summer and winter, respectively).…”
Section: Physico-chemical Characters Of Burullus Lagoonsupporting
confidence: 91%
“…It was also related to the increase in the orthophosphate and total phosphorus contents in the central sector. The dissolved salt (PO 4 ) concentrations in the middle basin were higher than those reported for the eastern and western sectors (Younis & Nafea, 2012;Melegy et al, 2019). Higher protein and carbohydrate concentrations were accompanied by the dominance of Chlorophyceae (Boëchat & Giani, 2000).…”
Section: Phytoplankton Biochemical Contentsmentioning
confidence: 84%
See 1 more Smart Citation
“…In order to place the Marchica Lagoon in a regional context of trace-element pollution status, a comparison was made with other Mediterranean lagoons (Table 6). The comparison showed that the maximal concentrations of Pb, Zn, and Cu recorded in the Marchica Lagoon were higher than those in Bizerte Lagoon, as reported by Barhoumi et al (2016) [83]; Berre Lagoon, as reported by Arienzo et al (2013) [84]; Izmit Bay, as reported by Tan et al (2020) [85]; Prokopos Lagoon, as reported by Katsaros et al (2017) [86]; Málaga Bay, as reported by Castillo et al (2013) [13]; Santa Gilla Lagoon, as reported by Atzori et al (2018) [87]; Burullus Lake, as reported by Melegy et al (2019) [88]; and Gialova Lagoon, as reported by Kanellopoulos et al (2020) [89].…”
Section: Discussionmentioning
confidence: 65%